2012
DOI: 10.1111/j.1751-1097.2012.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the Physiological Role of Anthocyanins in the Leaves of Coffea arabica

Abstract: The aim of this study was to determine which anthocyanins are related to the purple coloration of young leaves in Coffea arabica var. Purpurascens and assess their impact on photosynthesis as compared to C. arabica var. Catuaí, with green leaves. Two delphinidin glicosides were identified and histological cross-sections showed they were located throughout the adaxial epidermis in young leaves, disappearing as the leaves mature. Regardless the irradiance level, the photosynthetic performance of Purpurascens lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Similar results for epicatechin, mangiferin isomangiferin, procyanidin B, rutin, and quercetin glucoside derivatives contents were reported in coffee leaves (Almeida et al, 2014) [7]. In addition, coffee leaf samples in this study contained seven (i.e., caffeine, quercetin glucoside, rutin, mangiferin, isomangiferin, catechin, and epicatechin) bioactive compounds reported in commercial coffee leaves [1,4,5,6].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results for epicatechin, mangiferin isomangiferin, procyanidin B, rutin, and quercetin glucoside derivatives contents were reported in coffee leaves (Almeida et al, 2014) [7]. In addition, coffee leaf samples in this study contained seven (i.e., caffeine, quercetin glucoside, rutin, mangiferin, isomangiferin, catechin, and epicatechin) bioactive compounds reported in commercial coffee leaves [1,4,5,6].…”
Section: Resultssupporting
confidence: 87%
“…Coffee leaf tea has higher antioxidant potential and lower caffeine than traditional tea. The polyphenol content of coffee leaf depends on the maturity, the harvest times (month of harvest), and the coffee species of its leaf and are phytochemically composed of caffeine, trigonelline, adenine-7-glucosyl, theobromine, theophylline, ent -kaurane diterpenpids, 7-methylxanthine, anthocyanins, mangiferin, isomangiferin, catechin, epicatechin, procyanidin B1, chlorogenic acid (5-CQA), glucoside, rutin, isorhamnetin, quercetin, isoquercitrin, kaempferol, histidine, pipecolic acid, sucrose, tannins, caffeic acid, p-coumaric acid, ferulic acid, sinapic acid, neochlorogenic acid (3-CQA), and cryptochlorogenic acid (4-CQA) [1,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of compounds such as anthocyanins in Coffea arabica var. Purpurascens, prevents degradation of isomers of chlorogenic acid exposed to UV radiation (Domingues Júnior et al, 2012). The hydroxycinnamic acids content in C. arabica is higher than in other species such as Coffea sessilifl Bridson, Coffea resinora Hook.…”
Section: Phytochemicals Compounds Reported In Coffea Leavesmentioning
confidence: 98%
“…Chen et al identified delphinidin 3,5-diglucoside (10) and delphinidin 3-(6"-malonyl-glucoside) (11) in the young leaves of C. arabica L. [6] Besides the above mentioned constituents, flavonoids and their glycosides were also isolated from the leaves of C. arabica L., which were named as cyanidin-3-O-Glu (12), cyanidin-3-O-rutinoside (13), kaempferol (14), kaempferol-3-O-Glc (15), kaempferol-3-O-Glc-Hex-DeHex (16), kaempferol-3-O-Glc-Hex (17), kaempferol-3-O-Glc-(6''-Rha) (18), quercetin (19), quercitrin (20), isoquercitrin (21), rutin (22), hyperoside (23), quercetin-3-O-Glc-Hex-DeHex (24), quercetin-3-O-Glu (25), luteolin (26), patuletin (27), fisetin (28), myricetin (29) and apigenin (30). [6][7][8][9] Their structures are shown in Figure 2.…”
Section: Flavonoidsmentioning
confidence: 99%